ANALISIS PUTUSAN PENGADILAN TINGGI AGAMA SURABAYA DALAM PERKARA GUGATAN EKONOMI SYARIAH TENTANG WANPRESTASI AKAD AL QARDH DAN AKAD IJARAH (STUDI KASUS PUTUSAN PERKARA NOMOR 0223/Pdt.G/2015/PTA.Sby) - Ummi Nurjannah Prastyawati; Abdul Wahab (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2020)
ABSTRACTIn connection with the Sharia Economy referred to in article 49 of Law number 3 of 2006 letter (i) above, that Sharia Economy in actions or business activities carried out according to sharia principles. Then all sharia financing institutions and financial customers or conventional banks that open the sharia business sector, are naturally bound to sharia economic benefits.With the formulation of the problem: first, What is the main case number : 0223 / Pdt.G / 2015 / PTA.Sby Surabaya religious court about the breach of the Akad al Qardh and Akad Ijarah contracts, Second, What is the legal basis of the judges of the Surabaya Religion Court in decide the Islamic economic dispute case number : 0223 / Pdt.G / 2015 /PTA.Sby, Third, What is the decision of the Judge regarding the Al Qardh Akad Performance and Akad Ijarah in the Case Verdict Case Number : 0223 / Pdt.G / 2015 / PTA.Sby.By using the normative juridical descriptive research method which is an approach that uses a positivist juridical conception, namely that the law is identical to the written norm made by the authorities, so far the law has been made as a normative system that is autonomously closed and independent of people's lives. Based on the research results that are considered by Judges in the decision number : 0223 / Pdt.G / 2015 / PTA. By the source of the law used is Law number 7 of 1989 as amended by Article Law Number 3 of 2006 and the second amendment to Law Number 50 of 2009, Law Number: 1 of 1995 concerning limited liability companies, compilation of Sharia Economic Law (KHES) and HIR.Â Key Word: Analysis of Court Decisions, Akad Al Qardh and Akad Ijarah